Tree Species Diversity Status and Contributors to Forest Degradation in Shasha Forest Reserve, Nigeria (Global Journal of Science Frontier Research, 2023)
Deforestation and forest degradation are related to human-induced activities practiced compared to the conservation of forests and their management in Nigeria. This work evaluated the diversity status of tree species in Shasha Forest Reserve utilizing a simple random sampling method for plot differentiation, with a transect established in the assessment area. Sixteen sample plots of 25 m x 25 m were found within the minimally protected and unprotected plots of the reserve. Descriptive statistics were used to analyze the data generated. The results of the tree appraisal showed that 644 individual trees and 60 different tree species (23 families) were identified. The tree species diversity indices obtained were (3.855 and 0.596) for Shannon-Weiner and species evenness, respectively. Rauvolfiavomitoria of the family Apocynaceae (46) was the most predominant tree species, followed by Celtiszenkeriof, the family Ulmaceae (32), and the families with the highest number of species were Sterculiaceae (8) and Euphorbiaceae (7).
Keywords: cropland; deforestation; forest degradation; forest management; ecological community; tree species diversity indices